Mobbing Towards Health Workers - Yiğitbaş, Çağla; Deveci, Süleyman Erhan (Türk Tabipleri Birliği, 2011)
Mobbing has been recognized as a major occupational stressor since the mid 1980s. Such treatment tends to stigmatise the target and may causesevere psychological trauma. Mobbingin work placecan be defined as a form of psychological harassment and terror arising from one or more than twoperson’s unethical behaviour and leading to victimization of the worker. It is an increasing worldwide problem which is still largely unknown andunderestimated. It can produce serious negativeconsequences on the quality of life, and on individuals' health, mainly in the emotional, psychosomatic and behavioural areas. Mobbing in hospitalsnot only diminishes the quality of service but alsocauses the health personnel to work in unpleasantenvironments. The reduction of mobbing activities in healtcare yields patient and health personel satisfaction at the same time and ensures that the hospitals can provide the high quality services which are expected from them.

Özet Mobbing, 1980’lerin ortalarından itibaren mesleki anlamda başlıca stres kaynağı olarak tanımlanmaktadır. Davranış hedef kişiyi damgalamaya yöneliktir ve birçok psikolojik travmaya neden olabilmektedir. İşyerinde mobbing, bir veya birkaç kişi tarafından bir bireyi hedef alıp sistematik bir biçimde düşmanca ve ahlak dışı davranışlar şeklinde ortaya çıkan bir çeşit psikolojik terör olarak tanımlanmaktadır. İşyerinde mobbing kamu ve özel sektörlerde çalışanların psikolojik ve fiziksel sağlıklarını bozan baskıcı davranışlardır. Hastanelerde yaşanan mobbing olayları hem hizmetin kalitesini etkilemekte hem de sağlık çalışanlarının mutsuz ortamlarda çalışmalarına neden olmaktadır. Mobbing gibi durumların önemli bir hizmet sektörü olan sağlık alanında azaltılması hasta ve çalışan memnuniyetini bir arada sağlamakta ve hastanelerden beklenen hizmet üst seviyede sağlanabilmektedir. Anahtar kelimeler: Duygusal şiddet, mobbing, sağlık çalışanı. Mobbing Towards Health Workers Abstract Mobbing has been recognized as a major occupational stressor since the mid 1980s. Such treatment tends to stigmatise the target and may cause severe psychological trauma. Mobbingin work place can be defined as a form of psychological harassment and terror arising from one or more than two person’s unethical behaviour and leading to victimization of the worker. It is an increasing worldwide problem which is still largely unknown and underestimated. It can produce serious negative consequences on the quality of life, and on individuals' health, mainly in the emotional, psychosomatic and behavioural areas. Mobbing in hospitals not only diminishes the quality of service but also causes the health personnel to work in unpleasant environments. The reduction of mobbing activities in healtcare yields patient and health prsonel satisfaction at the same time and ensures that the hospitals can provide the high quality services which are expected from them. Key words: Emotional abuse, mobbing, health care worker.
SAĞLIK ÇALIŞANLARINA YÖNELİK MOBBİNG